Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2015)
(Abstract only. Link to: http://newprairiepress.org/kaesrr/vol1/iss3/7/) Article is nearly identical to Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn, previously published in Kansas Fertilizer Research 2015, included in this PDF. Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2014, N applied alone increased yields 58 bu/a, whereas P applied alone increased yields only 12 bu/a. Nitrogen and P applied together increased yields up to 152 bu/a. This is slightly above the 10-year average, when N and P fertilization increased corn yields up to 146 bu/a. Application of 120 lb/a N (with P) produced about 91% of maximum yield in 2014, which was similar to the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields 9 bu/a.
Keywords: soil fertility; irrigation; corn; nitrogen fertilization; phosphorus fertilization